الهوية الرقمية والأمن الهوياتي الجزائري في ظل تحديات المجتمع الشبكي: "الثابت والمتغير" - بلاغماس, اسماء (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
تشكل وسائل الاعلام والاتصال الرقمية العامل الأهم في تكوين اتجاهات ومواقف الفرد باعتبارها الطريق إلى المعرفة والأداة الفعالة في التنمية وتطوير الوعي، وقد أفرزت ثورة تكنولوجيا الاعلام والاتصال نمطا جديدا من المجتمعات وهو المجتمع الشبكي أو الرقمي الذي فتح المجال لتداول نماذج ثقافية متعددة، ويهتم هذا المقال بالتحديات التي تواجهها الهوية الجزائرية في هذا العالم الرقمي الجديد، وهذا نظرا للتحولات الجذرية التي أصبح يعيشها المجتمع الجزائري نتيجة تداخل المحلي بالكوني، وكذا المد الذي تفرضه العولمة حيث يجد الفرد نفسه بين هوية ثقافية أصلية يسعى للحفاظ عليها وأخرى وافدة قد تعزله أو تهيمن عليه، وقد توصلنا إلى أن جيل الانترنيت أصبح يظهر كجيل ثنائي الهوية: هوية رقمية تفرض عليه متابعة المستجدات العالمية التي تكسبه وجوده الافتراضي وتمنحه مواطنة عالمية، وهوية حقيقية تعيد ربطه بواقعه وبمجتمعه المحلي. الكلمات المفتاحية: الهوية؛ الهوية الرقمية؛ الأمن الهوياتي؛ المجتمع الشبكي. Abstract: Media and communication are the most important factor in the formation of individual trends as the path to the knowledge, and the ICT revolution has produced a new paradigm of society: the networked community that has opened the way for the circulation of multiple cultural models. This article is concerned with the challenges faced by the Algerian identity in this digital world and this is due to the radical transformations that Algerian society is experiencing as a result of the interference of local with the universe, as well as the tide imposed by globalization, where the individual finds himself between an original cultural identity seeking to preserve it and an expatriate that may dominate it, and we have concluded that the internet generation has become emerging as a binary generation: a digital identity that forces him to follow the global developments gained by his virtual existence and give him a real citizenship and a universal identity that reconnects him to his reality and society Local. Keywords: Identity; Digital Identity; Identity Security; networked society